Interactions of insect pests, diseases, and Sub1 rice varieties across agro-climatic zones in Assam: insights for strengthening resilient rice cultivation - Srinivasan, Thanga Suja; Peramaiyan, Panneerselvam; Peñalver-Cruz, Ainara; Khandai, Suryakanta; Kumar, Vipin; Kumar, Vivek; Saikia, Mrinal; Pathak, Kalyan; Borgohain, Rupam; Singh, Kanwar; Ahmed, Shabrin Sultana; Goswami, Gayatree; et al. (Frontiers in Sustainable Food Systems, 2025)
This study investigates the prevalence and interaction of insect pests and diseases across the agro-climatic zones of Assam, which are deployed with submergence-tolerant (Sub1) rice varieties. Utilizing data collected from farmers’ fields over 2 years (2020 and 2022), the research provides novel insights into how host genotype and climatic zones influence insect pests and disease prevalence under real-world conditions. The results reveal significant variability in insect and disease incidence across different agro-climatic zones and among rice varieties. The Central Brahmaputra Valley (CBV) zone exhibited a higher prevalence of insect pests such as the L. acuta, S. incertulas, and C. medinalis, while the Lower Brahmaputra Valley (LBV) zone demonstrated increased disease incidence, particularly of M. oryzae and B. oryzae. Similarly, varietal responses varied across agro-climatic zones; Bahadur-Sub1 exhibited comparatively lower insect and disease incidence, whereas Bina dhan 11 showed higher L. acuta and C. medinalis incidence across zones. Principal component analysis underscored zone-specific associations between insect pests and diseases, emphasizing the complex interactions among host plants, agro-climatic conditions, and insect-pest population buildup. Temporal variation was also observed, with differences in insect pests and disease prevalence between the 2 years, highlighting the impact of macro and micro-climatic factors. These findings suggest continuous monitoring and development of adaptive, zone-specific insect and disease management strategies that can minimize insect-pest adaptation and enhance the resilience and productivity of rainfed rice ecosystems in Assam.